Ensaios em economia política: efeitos dos incentivos eleitorais e da restrição de acesso ao crédito rural - Amarante, José Carlos Araújo (2022)
This thesis is composed of two essays related to problems of political economy. In the first essay, the hypothesis is assumed that mayors can manipulate the quality of public services offered by controlling spending and the level of effort spent on their actions. Based on these assumptions, the main objective is to empirically analyze the influence of electoral incentives on general municipal development and on the development of the health, education and employment and income segments. To this end, an econometric study was carried out based on panel data from Brazilian municipalities during two municipal administrations: 2009-2012 and 2013-2016. The main results found suggest that reelection can work as an instrument to control voters over the level of effort of elected politicians for executive positions. Likewise, in some cases, secondterm mayors may put more effort into delivering public services in order to keep their party in charge of the municipality. Additionally, the results also indicate that, in electoral years, the level of effort of politicians in general municipal development and in the development of the employment and income segment increases. In turn, the objective of the second essay is to analyze the effect of rural credit restriction policies implemented with Resolution 3,545/2008 on forest fires in the Amazon Biome. This resolution restricted access to rural credit to producers in the Amazon Biome who were following the environmental preservation laws instituted by Brazilian environmental agencies. To measure the impact of the rural credit restriction policy, the differences in differences approach was used in a data panel with monthly information on the treatment and control groups between 2005 and 2020. The results found allow us to infer that the impact of Resolution 3,545 /2008 on forest fires in the Amazon Biome was positive, as estimates indicate a reduction in the frequency of forest fires from the period in which the policy was implemented until the end of the period covered by this study.